Communicative Language Teaching Method to Foster English Oral Production on Senior High School Students - Ascanta Otacoma, Martha Sarina (2022)
To analyze the influence of Communicative Language Teaching method in the enhancement of English Oral Production on senior students at Colegio Universitario “UTN” in Ibarra, school year 2021-2022